Stress-strain behaviour of high-strength concrete with lateral pre-tensioning confinement [electronic resource] - Abdullah Zawawi Awang, 1964-; Wahid Omar, supervisor; Fakulti Kejuruteraan Awam (2013)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2013